2015
DOI: 10.1017/s1474746415000457
|View full text |Cite
|
Sign up to set email alerts
|

Which Employers Offer Hope for Mainstream Job Opportunities for Disabled People?

Abstract: Employer reluctance to hire disabled people narrows the economic and vocational opportunities of disabled people. This study investigates employer hiring decisions to identify which mainstream employers are most likely to hire disabled people. The study reports findings from interviews with eighty-seven employers in urban and regional South Australia. Analysis reveals differences across groups of employers based on their previous hiring behaviour. Communication from employment support agencies should specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 42 publications
0
36
1
Order By: Relevance
“…It has been suggested that even if people with disabilities eventually make it into applicant pools, hiring managers might incorrectly assume that these applicants do not want challenging careers or assignments (Perry, Hendricks, & Broadbent, 2000;Wilson-Kovacs et al, 2008). Worse, one prejudice that continues to affect people with disabilities is that they are perceived to not want to work at all (Hemphill & Kulik, 2016). These biases permeate decisions in all phases of the employment cycle.…”
Section: Concern 3: the Attractiveness Of Job Openings To People Withmentioning
confidence: 99%
“…It has been suggested that even if people with disabilities eventually make it into applicant pools, hiring managers might incorrectly assume that these applicants do not want challenging careers or assignments (Perry, Hendricks, & Broadbent, 2000;Wilson-Kovacs et al, 2008). Worse, one prejudice that continues to affect people with disabilities is that they are perceived to not want to work at all (Hemphill & Kulik, 2016). These biases permeate decisions in all phases of the employment cycle.…”
Section: Concern 3: the Attractiveness Of Job Openings To People Withmentioning
confidence: 99%
“…Second, little is known about employers' experiences of providing accommodations to YWD. Most research has focused on their attitudes towards hiring people with disabilities and not their actual practices of hiring and including people with disabilities (Burke et al, 2013;Fraser et al, 2010;Hemphill & Kulik, 2015). Developing an understanding of disclosure and accommodations experiences can help young workers to succeed in finding and maintaining employment, especially at this critical early stage of their careers (Lindsay, Adams, et al, 2014;Lindsay, Cagliostro, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The second important set of problems includes assessing personal and professional potential of people with disabilities for hiring. One of the most common prejudices that affect people with disabilities and special needs is that they are perceived by employers as not willing to work at all [31]. Many employers hold poorly grounded stereotypical views on the potentials of people with disabilities that often permeate the entire work cycle.…”
Section: Major Problems and Possible Solutionsmentioning
confidence: 99%